IMPLEMENTASI KURIKULUM BERBASIS TEKNOLOGI MELALUI PENGUATAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Gebbriellia Rosiana Ramadhani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to analyze the implementation of a technology-based curriculum through the strengthening of digital literacy of elementary school students in a case study at NH Elementary School. The study uses a qualitative approach with a case study method. Data were collected through interviews with the school principal and a fourth-grade teacher, classroom observations, and analysis of school curriculum documents. The results show that the use of technology at NH Elementary School is still instrumental and has not been integrated into a systematic digital literacy framework. The main limitation lies in teachers’ readiness to design technology-based learning frameworks, so learning tends to be passive. This study produces a one-semester mini digital literacy curriculum design as a model for strengthening more structured technology-based learning.